2011
DOI: 10.1016/j.juro.2010.10.076
|View full text |Cite
|
Sign up to set email alerts
|

D'Amico Risk Stratification Correlates With Degree of Suspicion of Prostate Cancer on Multiparametric Magnetic Resonance Imaging

Abstract: Objective We sought to determine if there is a correlation between D'Amico risk stratification and degree of suspicion of prostate cancer on multi-parametric MRI, based on targeted biopsies obtained with our electromagnetically (EM) tracked MRI/ultrasound (US) fusion platform. Methods 101 patients underwent 3 Tesla multi-parametric MR imaging of the prostate which consisted of T2, DCE, DWI, and spectroscopy images in patients with a suspicion for, or diagnosis of prostate cancer. All prostate MRI lesions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 107 publications
(76 citation statements)
references
References 27 publications
3
69
0
1
Order By: Relevance
“…Giderek artan bilimsel veriler, MR-TRUS füzyon biyopsisi ile klinik anlamlı kanser tanısının arttığını, bunun yanı sıra klinik anlamsız kanser tanısının da azaldığını göstermektedir (13,16). Bu da uygulanan prostat biyopsisinin hedefine ulaşması olarak kabul edilebilir.…”
Section: Sonuçunclassified
“…Giderek artan bilimsel veriler, MR-TRUS füzyon biyopsisi ile klinik anlamlı kanser tanısının arttığını, bunun yanı sıra klinik anlamsız kanser tanısının da azaldığını göstermektedir (13,16). Bu da uygulanan prostat biyopsisinin hedefine ulaşması olarak kabul edilebilir.…”
Section: Sonuçunclassified
“…Turkbey et al 11 reported that multiparametric MRI has a positive predictive value of 98% to 100% and 68% sensitivity for detecting prostate cancer tumors > 5 mm in diameter. A study by Rastinehad et al 12 reported 94% sensitivity for lesions in the peripheral zone of the prostate, with 99% specificity using multiparametric MRI. MRI/ultrasound fusion-guided biopsy is a more recent imaging modality that is under investigation.…”
Section: Evaluation Of Patients For Focal Therapymentioning
confidence: 99%
“…Despite these results MRGB remains controversial due to impracticalities, as its low availability, required expertise and time consuming nature. An upcoming technique is MRI-TRUS fusion (MTF) targeted biopsy [28][29][30][31][32][33][34][35][36][37][38]. MTF devices utilise the high diagnostic yield of the mpMRI for prostate cancer in combination with the practicality and affordability of TRUS biopsy systems by fusing the pre-interventional MR images with real-time ultrasound images.…”
Section: Introductionmentioning
confidence: 99%
“…The mpMRI information is used 'cognitively' by the physician to target tumour suspicious areas of the prostate using TRUS without applying image fusion [39,40]. All these techniques demonstrate an increased TDR of significant prostate cancer compared to systematic TRUS biopsy [17,[25][26][27][28][29][30][31][32][33][34][35][36][39][40][41][42]. There is no consensus which technique for targeted biopsy should be preferred.…”
Section: Introductionmentioning
confidence: 99%